Leisure time physical activity and health-related behaviours after liver transplantation: a prospective, single-centre study - Kotarska, Katarzyna; Wunsch, Ewa; Raszeja-Wyszomirska, Joanna; Kempińska-Podhorodecka, Agnieszka; Wójcicki, Maciej; Milkiewicz, Piotr (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Leisure time physical activity is of proven significance in surveys of fitness levels in various patient groups. Low physical functioning may affect recovery after liver transplantation (LTx). Aim: To assess patients’ leisure time activity and health-related habits after transplantation. Material and methods : One hundred and seven patients after LTx were included. They were divided into groups depending on aetiology of liver problem and the period after LTx. Minnesota Leisure Time Physical Activity Questionnaire (MILTPAQ) and Health Behaviour Inventory (HBI) were applied. Results: Neither the primary indication for the procedure nor the period after surgery had a significant relationship with physical activity assessed with MILTPAQ; however, activity was lower in females than males (1804.3 ±1848.9 vs. 2619.9 ±2067; p = 0.03). Age at survey/surgery was inversely associated with higher activity (p = 0.02 and p = 0.03, respectively). Health Behaviour Inventory analysis showed a correlation between all four of its domains and age at transplantation/survey (p < 0.001 for both). There was a negative correlation between positive mental attitude and body mass index (BMI). Conclusions : The primary indications for grafting and, surprisingly, the period after surgery did not seem to be related to the patients’ physical activity in leisure time. Younger and leaner patients appeared to understand the standards of healthy behaviour better and implement them in their daily activities. As higher BMI are associated with a negative mental attitude in patients after LTx, a particular emphasis should be placed on proper counselling in this subgroup of patients.